Moral progress and the epistemic vices of corporations - Ng, Bryson Pei Shen (Nanyang Technological University, 2025)
Recent years have seen a resurgence of philosophical interest in the concept of moral progress. While much extant research focuses on the normative causes or reasons behind moral progress, relatively less emphasis has been placed on the epistemic impediments to moral progress. In this thesis, I aim to contribute to this paucity of philosophical attention by explicating one previously underexplored epistemic impediment: the epistemic vices of business corporations (henceforth just ‘corporations’). Today, the global pervasiveness of corporations is indubitable; yet no philosophical analysis of how such corporations may affect moral progress currently exists. Drawing on Cassam’s obstructivist account of epistemic vice, I argue that the collective epistemic vices of corporations may impede the development of moral progress. This is because powerful corporations not only exhibit, but even operationalise such epistemic vices in ways that are inimical to the epistemic conditions required for further moral progress. My account explores one specific type of epistemic vice found in corporations: epistemic malevolence. I will examine the moral-epistemic impacts of the epistemic malevolence of corporations on two paradigmatic moral issues that we still face today: animal rights and climate change.